Life History of the Diatom Schizostauron trachyderma: Cell Size and Lipid Accumulation - Górecka, Ewa; Dąbek, Przemysław; Davidovich, Nikolai; Davidovich, Olga; Tremblay, Réjean; Belzile, Claude; Gastineau, Romain; Witkowski, Andrzej (Frontiers in Marine Science, 2022)
The focus of this study was to determine the mating type of Schizostauron trachyderma and examine the relation between cell size (life cycle), lipid droplet size and lipid content among diatoms with similar cell dimensions. To accomplish that, we have chosen monoclonal cultures of two closely related diatom species, namely S. trachyderma and S. rawaii. In a series of experiments, we successfully induced sexual reproduction within S. trachyderma strains in order to reconstruct the whole cell cycle involving cells of the maximum (initial cells) and minimum viable size for a given species. The mating type and sexual reproduction stages were described and documented. A unique experimental setting involved initial cells isolation and their lipid droplets examination by means of flow cytometry and confocal microscopy after Nile Red staining. The results of the series of experiments indicate correlations between cell size, the amount of neutral lipids per cell and the size of lipid droplets, suggesting that cells capacity for lipids accumulation is dependent on their position in the life cycle.